Some Cataloging Or Real Cataloging !? cataloging remotely accessed electronic resources : a viewpoint for discussion - Tolaib, Hesham (Cybrarians Journal, 2004)
Abstract This paper presents a viewpoint about cataloging Remotely Accessed Electronic Resources , Starting with revealing a professional personal experience , then it deals briefly with the field scene discussing some of its solutions , suggestions , and sub-issues of the main issue . The paper critically treats AACR2 and its adaptation for cataloging those resources , especially 2002 Revision . Ending with presenting a new vision about the adaptations needed to solve the issue , exploring types of adaptations and its areas , it proposes a dichotomy for the code . Finally it presents a preliminary frame to implement such a vision .